The Use Of Instagram As A Media To Improve Students’ Writing Skills In Descriptive Text At The Tenth Grade Of Sma Negeri 5 Pematang Siantar 2023 - Anita Purba; Rohdearni Wati Sipayung; Dinda Inayan (Program Studi Pendidikan Bahasa Inggris FKIP, 2023)
This research was aimed at investigating to improve students’ in writing ability using Instagram as media. at the tenth grade of SMA Negeri 5 Pematang Siantar. The problem of the research is Does the use of Instagram as a Media can improve students writing skills in descriptive text at the tenth grade of SMA Negeri 5 Pematang Siantar for the academic year 2022/2023 ?. The objective of the research is to find whether the use on Instagram as a Media can improve students’ writing skills in descriptive text at the tenth grade of SMA Negeri 5 Pematang Siantar for the academic year 2022/2023. The research was quantitative research. For the data collection, there were pre-test and post-test. The population of this research 360 students’ in research academic year 2022/2023 with of 36 students’ was the sample. The data analysis was at tenth grade students’ stared from scoring pre-test and post-test and finding the different mean of the score. Based on the data analysis, the writer finding pre-test students’ mean score only 60,75 and after the treatment, the writer used to post-test to know students’ improve writing ability score. The result of the test found the average of the pos-test mean score test was 81,03. The teachers may try to take advantage of the use of Instagram as media to be utilized in their classroom activities to conduct an effective and interesting learning atmosphere in the classroom. So the students’ felt comfortable and enjoyed to learn so that gives a good impact on writing English skills